2019
DOI: 10.15671/hjbc.585877
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Anatomical Survey on the species of Iberis L. (Brassicaceae) from Turkey

Abstract: T ürkiye'de doğal olarak yetişen Iberis cinsi ülkemizde 8 türle temsil edilmekte olup tek ve/veya çok yıllık otlar veya yarı çalılardan oluşmaktadır. Bu çalışmada, Türkiye'de yetişen Iberis taksonları anatomik olarak detaylı biçimde ilk defa çalışılmış ve bu sayede cinsle ilgili taksonomik belirsizlikler ve karmaşıklıklar çözülmeye çalışılmıştır. Iberis türlerinin kök, gövde, yaprak anatomileri çalışılmış ve stoma indeksi ortaya konmuştur. Bu çalışmada elde edilen sonuçlar, cinsin türleriyle ilgili şüpheli dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The number of vessels was the most crowded in I. halophila because of the characteristics of this halophytic species, not mentioned previously in Çilden and Zare (2019). Çilden and Zare (2019) indicated that I. carica had a perennial habit and isolateral leaf anatomy. However in this study, we confirmed that I. carica has a distinct annual herb with primary root anatomy.…”
Section: Numerical Analysis Of the Anatomical Character Statesmentioning
confidence: 75%
See 1 more Smart Citation
“…The number of vessels was the most crowded in I. halophila because of the characteristics of this halophytic species, not mentioned previously in Çilden and Zare (2019). Çilden and Zare (2019) indicated that I. carica had a perennial habit and isolateral leaf anatomy. However in this study, we confirmed that I. carica has a distinct annual herb with primary root anatomy.…”
Section: Numerical Analysis Of the Anatomical Character Statesmentioning
confidence: 75%
“…More specifically, obtaining plants with mature fruit is highly significant for separating genera in the family Brassicaceae. The genus Iberis is a small group in crucifers, with a total of 28 species in the world (Al-Shehbaz, 2012;Çilden and Zare, 2019). The total number of Iberis species in Turkey is nine (Mutlu, 2012;Oskay, 2017;Çıtak, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This study provided results relevant for the current taxonomy of the genus. In addition to the anatomical results of Çilden and Zare (2019), field observations, herbarium investigations, taxonomical literature and molecular results (Çilden and Özüdoğru, in evaluation) also give important evidence about the morphology and taxonomy of Iberis taxa in Turkey. As a result of these studies, the list of Iberis taxa from Turkey may be updated here with their current nomenclatural recognitions, and listed alphabetically: I. attica Jord., I. carica (Bornm.)…”
Section: Introductionmentioning
confidence: 99%
“…It also presents the karyogram and ideogram of the species. The first comprehensive study consisting of the comparative anatomical features based on current collections from 17 different populations from Turkey (Çilden and Zare 2019) comprises accurately identified specimens, especially endemics collected from their type localities. This study provided results relevant for the current taxonomy of the genus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation